Insurance Rating Games: Strikes, Spares, and Bags. Issue 2 (September 2014) - Ahlgrim, Kevin C.; Jones, James R.
Abstract Carefully designed classroom activities and games can be used to increase student engagement, motivation, and learning. This article describes two games that have been used with students of risk management and insurance to help highlight the intricacies of insurance pricing. These two games, bowling insurance and bags insurance, help students experience the challenging nature of premium determination in risk transfer contracts and also connect the various actions taken by insurers during the insurance transaction.